Analisis Faktor-Faktor yang Memengaruhi Return pn Asset serta Manfaat Ekonomi Anggota Koperasi - Rahmi, Anggita; Setiawati, Rosti (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study aims to explain the factors that influence the decline in return on assets and the economic benefits obtained by cooperative members. This research was conducted with the object of the trading business unit of Sumber Tani Mandiri Agricultural Cooperative. In this study, the method used is a case study by collecting data and direct observation on the object of research and then analyzing it in depth. The measuring instrument to determine the factors that influence the decline in return on assets uses net profit margin and total asset turnover. Meanwhile, direct economic benefits are measured by comparing prices in cooperatives and non-cooperatives. In addition, the economic benefit of direct members is analyzed by distributing questionnaires to cooperative members as respondents. Then, for indirect economic benefit, it was measured by calculating the remaining operating results of the members' share. The results showed that the turnover of total assets from 2018 to 2022, so that the turnover of total assets can be said to be effective because the turnover is getting faster. However, when viewed from the development of net profit margin, it is considered inefficient because the amount of net profit margin generated tends to decrease due to increased expenses or costs incurred. The amount of net profit margin generated in 2018 to 2022. Thus, the factors that influence the decrease in return on assets are due to expenses or costs that have increased more than revenue from sales. The direct economic benefits in the form of price benefits offered by cooperatives are cheaper than the prices offered by non-cooperatives. However, for indirect economic benefits in the form of the remaining results of operations has decreased from the previous year.